The challenges of rural youth employment in Africa: A literature review - Zaneta Kubik (University of Bonn, Center for Development Research (ZEF), 2022)
This paper provides a literature review on youth employment challenges in rural Africa. The rapidly changing demographic structure across the continent is expected to have important economic and social consequences, especially for employment. So far, despite sustained economic growth, African countries have not been successful in absorbing the fast-growing labor force, especially in the context of labor markets characterized by high levels of informality, underemployment and working poverty. As a consequence of life-cycle effects, relative to the measure of accumulated life experience; and generational effects, relative to the measure of the conditions prevailing during an individual's formative years, young people are exposed to several constraints in the labor market, including access to resources such as skills and innovation, finance and land. These challenges call for a comprehensive policy framework with complementary supply-side and demand-side interventions. Interventions that target girls and women can have particularly strong effects on their labor market outcomes. Food systems are increasingly recognized as potential catalyst for employment creation, given their future prospects and labor-intensive nature. Farming and self-employment in the agri-food sector are the dominant categories of youth employment in rural areas of Africa, and the latter is growing especially fast, even though it remains much lower than farming in absolute terms. Despite common perceptions, food system jobs play a significant role in youth's aspirations. Close to 25% of young Africans want to work in the food and agriculture sector, and the share is higher in some countries, close to 40% in Kenya, Liberia, Malawi and Tanzania. Accordingly, the average age of African farmers is not rising - it is also much lower than previously claimed, at 34 years of age and not 60. However, youth aspirations remain conditional on several factors that can make food system jobs attractive, including technology, investment, market opportunities, and decent earnings. Policies should prioritize interventions that will raise labor productivity in food system, along with the broader labor-market interventions.
Keywords: J13; J21; J22; J43; J48; 330; youth; labor force; employment; food systems; agriculture